2016
DOI: 10.1097/mpa.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Gemcitabine and Erlotinib Over Pancreatic Adenocarcinoma Cells

Abstract: Our data suggest that, although gemcitabine and erlotinib exert antiproliferative effects over pancreatic cancer cell lines, the gemcitabine-induced activation of NF-κB expression and its DNA-binding activities are important drawbacks of this treatment against pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Previous studies demonstrated that GEM inhibits the expression of cyclin D and Bcl-2, inducing G1 phase arrest in many types of human cancer cells including NSCLC. 27-29 Our results are consistent with these reports. The levels of cyclin D1 and Bcl-2 proteins were decreased in cells treated with GEM alone.…”
Section: Resultssupporting
confidence: 94%
“…Previous studies demonstrated that GEM inhibits the expression of cyclin D and Bcl-2, inducing G1 phase arrest in many types of human cancer cells including NSCLC. 27-29 Our results are consistent with these reports. The levels of cyclin D1 and Bcl-2 proteins were decreased in cells treated with GEM alone.…”
Section: Resultssupporting
confidence: 94%
“…Blockchain extension also exerts its anti‐tumor activity through a series of other cellular mechanisms on DNA synthesis. 18 , 19 Anlotinib is a multi‐target drug; however, the purpose of this study was to investigate the anti‐tumor mechanism of anlotinib combined with gemcitabine. To determine whether the inhibitory effect of anlotinib combined with gemcitabine on cell growth inhibition was due to cell cycle arrest, we analyzed the cell cycle distribution of these cells using FCM with PI/RNase staining.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that gemcitabine can cause S phase cell cycle arrest, and under certain conditions, it prevents the G1 phase transition to S phase. Blockchain extension also exerts its anti‐tumor activity through a series of other cellular mechanisms on DNA synthesis 18,19 . Anlotinib is a multi‐target drug; however, the purpose of this study was to investigate the anti‐tumor mechanism of anlotinib combined with gemcitabine.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent report suggested that median progression-free survival (PFS) and overall survival (OS) were improved with Nab-paclitaxel plus gemcitabine treatment in both locally advanced and metastasized PDAC, but hematologic toxicity was observed and dose reductions were performed in most of the patients [13,14]. Erlotinib, which acts as an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) and blocks its downstream signaling cascade to modulate cancer proliferation, differentiation, apoptosis, invasion, and metastasis, has been shown to increase the efficacy of gemcitabine towards radiation or recurrent PDAC tumor growth in mice [46][47][48][49][50]. Despite modest survival benefits observed from gemcitabine and erlotinib in clinical studies, combination treatment of gemcitabine and erlotinib was also approved for use in the advanced disease of PDAC, which prolongs 1-year survival by only 23% [17].…”
Section: Discussionmentioning
confidence: 99%